Resilience Education: Strategies for Coping with Failure and Academic Pressure Among High School Students in Sangihe Islands Regency, North Sulawesi - Agneta Sartika Lalombo (PT. Anagata Sembagi Education, 2025)
Resilience-based education has become increasingly relevant in addressing rising academic pressure among high school learners, particularly at the stage where cognitive and emotional demands intersect. This study examines the influence of resilience on academic stress and learning motivation among students of public senior high schools in the Sangihe Islands Regency, North Sulawesi, Indonesia. A quantitative approach was employed using Partial Least Square Structural Equation Modeling (PLS-SEM) with 120 respondents from grades X, XI, and XII. The findings indicate that resilience has a negative and significant effect on academic stress and a positive and significant effect on learning motivation. Students with higher resilience are better able to manage pressure from academic failure, maintain emotional balance, and foster a growth mindset that supports active participation in the learning process. These results show that resilience functions not only as a psychological defense mechanism against academic pressure but also as a motivational driver toward achievement. The study highlights the importance of integrating resilience education into classroom instruction and school counseling services to promote psychological well-being and academic success, especially in island regions with limited educational resources